Solitary pulmonary nodule: Comparison of quantitative capability for differentiation and management among dynamic CE-perfusion MRI at 3 T system, dynamic CE-perfusion ADCT and FDG-PET/CT. Issue 115 (June 2019) - Ohno, Yoshiharu; Fujisawa, Yasuko; Yui, Masao; Takenaka, Daisuke; Koyama, Hisanobu; Sugihara, Naoki; Yoshikawa, Takeshi
Highlights: Dynamic first-pass CE-perfusion ADCT and MR imaging with ultra-short TE have similar potential capabilities, and are superior to FDG-PET/CT for differentiation of malignant from benign nodules. The same results were also obtained in routine clinical practice for distinguishing nodules requiring aggressive intervention and treatment from those needing only follow-up examinations. When applied same mathematical model, dynamic first-pass CE-perfusion ADCT and MR imaging with ultra-short TE had same potential for pulmonary nodule evaluation. Abstract: Purpose: To prospectively compare the capability of dynamic first-pass contrast-enhanced (CE) perfusion MR imaging with ultra-short TE and area-detector CT (ADCT), analyzed with the same mathematical methods, and that of FDG-PET/CT for diagnosis and management of solitary pulmonary nodules (SPNs). Methods and materials: Our institutional review board approved this study and written informed consent was obtained from all subjects. A total 57 consecutive patients with 71 nodules prospectively underwent dynamic CE-perfusion ADCT and MR imaging with ultra-short TE, FDG-PET/CT, as well as microbacterial and/or pathological examinations. The nodules were classified into malignant nodules ( n  = 45) and benign nodules ( n  = 26). Pulmonary arterial, systemic arterial and total perfusions were determined by means of dual-input maximum slope models on ADCT and MR imaging and maximum values of standard uptake values (SUVmax ) on PET/CT. Receiver operating characteristic (ROC) analysis was performed for each index, and sensitivity, specificity and accuracy were compared by McNemar's test. Results: Areas under the curve (Azs) of total perfusion on ADCT (Az = 0.89) and MR imaging (Az = 0.88) were significantly larger than those of systemic arterial perfusion and MR imaging (p<0.05). Accuracy of total perfusion on ADCT (87.3% [62/71]) and MR imaging (87.3% [62/71]) was significantly higher than that of systemic arterial perfusion for both methods (77.5% [55/71] p  = 0.02) and SUVmax (78.9% [56/71], p  = 0.03). Conclusion: Dynamic CE-perfusion MR imaging with ultra-short TE and ADCT and have similar potential capabilities, and are superior to FDG-PET/CT in this setting.